2021
DOI: 10.9734/jpri/2021/v33i431166
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malaria with Anaemia and HIV Status in Women of Reproductive Age in Onitsha, Nigeria

Abstract: The major health problems affecting pregnant women in sub-Saharan African are anaemia, malaria and HIV. A case-control study aimed at determining the prevalence of malaria, anaemia and HIV status among women of reproductive age between 20-49 years attending General Hospital, Onitsha was conducted. Blood samples of three hundred and sixty-two apparently healthy gravid women attending antenatal and 181 non-gravid apparently healthy women in Onitsha were recruited using random sampling method. A structured questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Despite major advances in the treatment of HIV using HAART and survival of individuals infected with human immunodeficiency virus (HIV), negative energy remain common problems as seen in this study,which persisted even after 12 months of using HAART. This work supports Shevitz et al, [31], Fitch et al, [32], earlier report on energy expenditure in HIV subjects on highly active antiretroviral therapy [33][34][35][36].…”
Section: Discussionsupporting
confidence: 90%
“…Despite major advances in the treatment of HIV using HAART and survival of individuals infected with human immunodeficiency virus (HIV), negative energy remain common problems as seen in this study,which persisted even after 12 months of using HAART. This work supports Shevitz et al, [31], Fitch et al, [32], earlier report on energy expenditure in HIV subjects on highly active antiretroviral therapy [33][34][35][36].…”
Section: Discussionsupporting
confidence: 90%
“…And this was consistent with other study conducted in rural Uganda that has the same economic status with Nigeria which revealed that 42% of barrier to retention in care was distance [26]. Also, 21% of barrier to care utilization was found to be selfdenial and this outcome was similar to the previous study that stated that difficulty with selfacceptance affect the willingness to be retained [16], and finally, 7% of them did not utilize the care because they trusted in the efficacy of herbal medication [35][36][37][38][39][40][41].…”
Section: Discussionsupporting
confidence: 54%
“…More than half of the clients had a low CD4 cell counts (≤199.0 cells/ml) at the baseline assessment. Delayed access to HIV services for patients with low CD4 counts led to a higher death rate [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%